Operational Efficiency in Pakistan's Textile Industry: A Panel Data Analysis from 2018 to 2023 - Aiman Qamar; Dr. Khurram Iftikhar; Dr. Zia Abbas, (Dialogue Social Science Review (DSSR), 2025)
This study examines the operational efficiency of Pakistan's textile industry from 2018 to 2023 using panel data analysis. The findings provide a comprehensive view of the industry's overall technical efficiency (OTE), pure technical efficiency (PTE), and scale efficiency (SE) over time. Efficiency levels fluctuated across the years, influenced by internal managerial practices, resource allocation, and broader economic factors. The textile sector in Pakistan plays a pivotal role in the national economy, significantly contributing to exports and employment. To ensure continued growth and efficiency, it is essential to evaluate the operational performance of textile firms within the country. The input-oriented Banker-Charnes-Cooper (BCC) model of Data Envelopment Analysis (DEA) is employed to assess the efficiency of textile firms. The results show varying efficiency patterns, with the highest efficiency observed in 2021 and significant challenges in 2019 and 2023. Analysis of returns to scale revealed that many textile firms operated under constant returns to scale, while firm size positively impacted efficiency. These findings align with Sustainable Development Goal 9 by emphasizing the need for technological advancement, resilient infrastructure, and sustainable industrial practices. Furthermore, Policymakers would implement targeted incentives for small and medium-sized businesses to easily access financial support and a regulatory framework that promotes sustainability in order to further improve operational efficiency in the textile industry. In order to build a more competitive and sustainable textile industry in Pakistan, it would also involve collaborations between the public and private sectors on infrastructure development, research and innovation, and skill development.